2014
DOI: 10.4103/0973-1482.151487
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent involved-field radiotherapy and XELOX in gastric cancer patients with postoperative oligometastatic recurrence

Abstract: For patients with postoperative oligometastatic recurrence, concurrent involved-field RT and XELOX showed better responses and was a choice for first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A retrospective study showed that concurrent chemoradiotherapy in gastric cancer patients with local recurrence at the anastomic site or regional lymph nodes was associated with an ORR of 61.9% and mOS of 35 months [ 186 ]. Compared with chemotherapy alone, concurrent chemoradiotherapy resulted in a higher ORR (87.8% vs. 63.0%, P = 0.01), longer mOS (13.4 vs. 5.4 months, P = 0.06), and better control of symptoms such as pain, bleeding, and obstruction (85.0% vs. 55.9%, P = 0.06) [ 187 ]. c Recurrence in the remnant stomach after radical gastrectomy usually occurs within 10 years after surgery [ 188 ], and the possibility of resection is high.…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…A retrospective study showed that concurrent chemoradiotherapy in gastric cancer patients with local recurrence at the anastomic site or regional lymph nodes was associated with an ORR of 61.9% and mOS of 35 months [ 186 ]. Compared with chemotherapy alone, concurrent chemoradiotherapy resulted in a higher ORR (87.8% vs. 63.0%, P = 0.01), longer mOS (13.4 vs. 5.4 months, P = 0.06), and better control of symptoms such as pain, bleeding, and obstruction (85.0% vs. 55.9%, P = 0.06) [ 187 ]. c Recurrence in the remnant stomach after radical gastrectomy usually occurs within 10 years after surgery [ 188 ], and the possibility of resection is high.…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“… b For patients with local recurrence who did not receive any previous radiotherapy, concurrent chemoradiotherapy has been associated with survival benefits. A retrospective study showed that concurrent chemoradiotherapy in gastric cancer patients with local recurrence at the anastomic site or regional lymph nodes was associated with an ORR of 61.9% and mOS of 35 months [ 225 ]. Compared with chemotherapy alone, concurrent chemoradiotherapy resulted in a higher ORR (87.8% vs. 63.0%, P = 0.01), longer mOS (13.4 vs. 5.4 months, P = 0.06), and better control of symptoms such as pain, bleeding, and obstruction (85.0% vs. 55.9%, P = 0.06) [ 226 , 227 ].…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%